Pain sensitization associated with nonresponse after physiotherapy in people with knee osteoarthritis. Issue 9 (September 2018) - O'Leary, Helen; Smart, Keith M.; Moloney, Niamh A.; Blake, Catherine; Doody, Catherine M.
Abstract : Abstract: In knee osteoarthritis (OA), pain sensitization has been linked to a more severe symptomatology, but the prognostic implications of pain sensitivity in people undergoing conservative treatment such as physiotherapy are not established. This study aimed to prospectively investigate the association between features of pain sensitization and clinical outcome (nonresponse) after guideline-based physiotherapy in people with knee OA. Participants (n = 156) with moderate/severe knee OA were recruited from secondary care. All participants completed self-administered questionnaires and underwent quantitative sensory testing at baseline, thereby establishing subjective and objective measures of pain sensitization. Participants (n = 134) were later classified after a physiotherapy intervention, using treatment responder criteria (responder/nonresponder). Quantitative sensory testing data were reduced to a core set of latent variables using principal component analysis. A hierarchical logistic regression model was constructed to investigate whether features related to pain sensitization predicted nonresponse after controlling for other known predictors of poor outcome in knee OA. Higher temporal summation (odds ratio 2.00, 95% confidence interval 1.23-3.27) and lower pressure pain thresholds (odds ratio 0.48, 95% confidence interval 0.29-0.81) emerged as robust predictors of nonresponse after physiotherapy, along with a higher comorbidity score. The model demonstrated high sensitivity (87.8%) but modest specificity (52.3%). The independent relationship between pain sensitization and nonresponse may indicate an underlying explanatory association between neuroplastic changes in nociceptive processing and the maintenance of ongoing pain and disability in knee OA pain. These preliminary results suggest that interventions targeting pain sensitization may warrant future investigation in this population. Abstract : Enhanced temporal summation and lower pressure pain thresholds independently predicted nonresponse after a physiotherapy intervention for knee osteoarthritis.